Altering autotrophic carbon metabolism of Nitzschia closterium to mixotrophic mode for high-value product improvement. (March 2023) - Wang, Yuxin; Wang, Jia; Gu, Ziqiang; Yang, Shufang; He, Yongjin; Mou, Haijin; Sun, Han
Graphical abstract: Highlights: Red LED light was applied to realize mixotrophic domestication of N. closterium GM. N. closterium GM biomass increased by 1.46 folds compared with wide type. Glucose metabolism and tricarboxylic acid cycle were robust in N. closterium GM. Fucoxanthin and EPA productivity increased by 79.2% and 1.1-fold of N. closterium GM. Abstract: An adaptive laboratory evolution (ALE) strategy was designed to evolve autotrophic Nitzschia closterium to mixotrophic growth for high productivity of essential amino acid (EAA), eicosapentaenoic acid (EPA) and fucoxanthin. The N. closterium growth was limited under glucose initially, but a red light emitting diode was innovatively applied to modify carbon metabolism and obtain mixotrophic strain of N. closterium GM. The N. closterium GM biomass concentration was improved by 65.07% comparing with wild type, but exhibited weak photosynthesis and strong glucose metabolism. At carbon metabolism levels, ALE promoted NADPH oxidase activity and induced protein degradation to lipid biosynthesis by elevating acetyl-CoA and pyruvate contents. It also improved carbon flux to TCA cycle, and elevated contents of glucose-6-phosphate, fructose-6-phosphate, glyceraldehyde-3-phosphate for providing sufficient ATP and NADPH. Productivities of EPA, EAA and fucoxanthin were increased by 41.0%, 18.8% and 20.4%, respectively. This ALE strategy was promising in microalgal production of high-value products.